Panetary justice-old age: re-binding transepistemes in planetary decoloniality-complexity - Rodriguez, Milagros Elena (2023)
The imbricated union: planetary justice-complexity interprets the politics of humanity; the planetary anthropolitics imbricated in complex categories. For this reason, we base transepistemes of the dyad: planetary justice-old age with re-linkages in the planetary decolonial project and complexity; this is the complex objective of the investigation. Transmethodical inquiry with deeply disruptive rhizomatic deconstruction. Located in the lines of research: Planetary decoloniality-complexity in re-linkage and transepistemologies of knowledge-knowledge and transcomplex transmethodologies. In the reconstruction, transepistemes of planetary justice-old age are covered, such as: bioethics in its re-linkage in planetary decoloniality, planetary consciousness-ecosophy-bioethics-anthropoetic-anthropolitical; politics of civilization, and that means promoting complex strategies. In general, planetary-old age justice in the complex consideration of the human being contains an essential transepisteme, which is the wisdom housed in the soul-spirit, which God has provided to the human being. To understand the elderly we must do it from a complex thought, in which we can include everything that makes their person, essence and exist. And that promotes planetary justice in favor of any form of life. Give new meaning to the knowledge of old age and its activities towards the formation of new generations and the transcendence of their wisdom.